Epistemic beliefs and achievement goal orientations: Relations between constructs versus personal profiles. Issue 1 (2nd January 2017) - Madjar, Nir; Weinstock, Michael; Kaplan, Avi
ABSTRACT: Research has found students' epistemic beliefs to predict their achievement goal orientations. Much of this research emerged from the dimensional approach of epistemic beliefs, which hypothesized a relationship between particular independent dimensions of epistemic beliefs with different achievement goals. Research in this approach has primarily applied a variable-centered approach to investigating these relations. The authors adopt an alternative conceptualization of epistemic beliefs, which considers epistemic beliefs and achievement goals as orthogonal to each other, and which favors a profile-centered approach to researching their relations. They hypothesized that while a variable-centered analysis would identify relations between epistemic beliefs and achievement goal orientations, a profile-centered analysis would demonstrate the independence of these psychological constructs. In three studies with high school students ( n s = 256, 149, 250) the authors demonstrate that epistemic beliefs and achievement goals form different personal profiles that are differentially related to learning strategies.